LARANGAN SEBAGAI MEDIA PELESTARIAN HUTAN PADA KOMUNITAS ADAT CIKONDANG - Lasmiyati Lasmiyati; Ria Intani Tresnasih (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2023)
This research is conducted because of the frequent forest destruction occurrence, meanwhile, the forests in the Cikondang Indigenous Community area are still wellpreserved to date. This study aims to obtain an overview of the sacred grove located in Cikondang, the reason why the forest is designated as a sacred grove, and the factors that cause the forest to be well-preserved. This research is a descriptive one by exercising the qualitative method. The qualitative method isused to analyze objects that cannot be measured using numbers. The research methods were conducted by literature studies, observations, and interviews. Informants, both key and additional,were interviewed with reference to interview guidelines. The research stage is initiated by extracting the data in the field, classifying and analyzing the data, and finally drawing a conclusion. The results indicated that the forests in Cikondang physically have similarities with forests in general. Historical events and awareness of the benefits of the forest designated the forest as a sacred grove whose preservation has been well-maintained due to the enactment of a number of forbiddance or pamali related to the existence of the forest. Forbiddance or pamali is a customary rule that is obeyed because of fear of violating the forbiddance or pamali. It has the